Computer-based methods for cost estimation of underground electrical cable installation in Singapore - Ho, Teck Hong. (2009)
This thesis attempts to quantify the productivity aspect of conduits laying works under the PUB's power cable installation program. The objectives are two fold. Firstly, to study the environmental factors affecting the productivity of the works and quantify them formally and, secondly, to develop computer models for estimating the cost of such works.